The Loyalty of older people in fitness centers: Managing customers for physical activity programs - Jerónimo García Fernández; Francisco Pires Vega (FEADEF, 2010)
The fitness centers are now places where partners perform «controlled» physical activity, which improves their physical and mental state, and where they socialize with other partners of all ages. These centers have been typically managed by people without training in this subject and with the only interest of obtaining partners without taking into account the long-term impact. This problem, together with management problems of the center and personal problems of the members, have meant that there are high desertion rates in this type of indoor facilities, with the consequent increase in expenditure on marketing and a non-sustainable profitability. We propose a program of physical activity that could improve the rate of loyalty, being the central point of management of sports centers today, the satisfaction and loyalty to the fitness centers.